Sugar Levels Regulate Tryptophan-Dependent Auxin Biosynthesis in Developing Maize Kernels([C])([W])([OA]) - LeClere, Sherry (American Society of Plant Biologists, 2010)
The maize (Zea mays) Miniature1 (Mn1) locus encodes the cell wall invertase INCW2, which is localized predominantly in the basal endosperm transfer layer of developing kernels and catalyzes the conversion of sucrose into glucose and fructose. Mutations in Mn1 result in pleiotropic changes, including a reduction in kernel mass and a recently reported decrease in indole-3-acetic acid (IAA) levels throughout kernel development. Here, we show that mn1-1 basal kernel regions (pedicels and basal endosperm transfer layer) accumulate higher levels of sucrose and lower levels of glucose and fructose between 8 and 28 d after pollination when compared with the wild type, whereas upper regions of mn1 accumulate similar or increased concentrations of sugars. To determine the cause of the reduction in IAA accumulation, we investigated transcript levels of several potential IAA biosynthetic enzymes. We demonstrate that reduced IAA levels most closely correspond to reduced transcript levels of ZmYUCCA (ZmYUC), a newly identified homolog of the Arabidopsis (Arabidopsis thaliana) gene YUCCA. We further demonstrate that ZmYUC catalyzes the N-hydroxylation of tryptamine and that sugar levels regulate transcript levels of ZmYUC, both in in vitro-cultured kernels and in a promoter-reporter fusion in Arabidopsis. These results indicate that developing seeds may modulate growth by altering auxin biosynthesis in response to sugar concentrations.